TINJAUAN HUKUM KETERBUKAAN RAHASIA KEDOKTERAN DAN IDENTITAS PASIEN PADA SITUASI WABAH PANDEMI COVID-19 - Nur Syamsu Dhuha (Magister Ilmu Hukum, Universitas Wisnuwardhana Malang, 2020)
The Covid-19 pandemic is still ongoing in Indonesia. The accumulation of Covid-19 cases is still increasing even though efforts to prevent its spread have been made. The implementation of handling caused several polemics in the community, one of which was about the openness of patient data. The secret disclosure of medicine in the condition of the outbreak (including name, address, diagnosis, family history, and so on) without the patient's consent may pose a risk to the patient concerned. Patients can receive negative stigmatization or discrimination if the medical secrets are spread in the general public. The spread of medical secrets can also have legal implications for health workers as well as the general public involved in its spread. Handling medical secrets needs to be done carefully by considering the legal aspects and ethics of medicine. The problem taken is how is the legal review of the secret disclosure of doctors during the Covid-19 pandemic outbreak situation? This type of research uses normative juridical methods with a legal approach. The results of the review show that health workers have an obligation to maintain medical secrets as applicable laws and regulations. Violations of such obligations may be subject to ethical sanctions, disciplinary sanctions and legal sanctions. Medical secret can be opened under certain conditions, namely for the benefit of the patient's health, in the framework of law enforcement, at the request of the patient himself and in the public interest. The public interest in question, among others, is when there is a threat of Extraordinary Events / outbreaks of infectious diseases and threats to the safety of others individually or in the community. The opening of patient secrets can certainly only be done by authorized officers and given to agencies / authorities as well. Keywords: Openness, patient data, covid 19